Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]x^3+6x^2+5x-12=x^3-x^2+7x^2-7x+12x-12=\\\\=x^2(x-1)+7x(x-1)+12(x-1)=(x-1)(x^2+7x+12)=\\\\=(x-1)(x^2+3x+4x+12)=(x-1)[x(x+3)+4(x+3)]=\\\\=(x-1)(x+3)(x+4)[/tex]
x³ + 6x² + 5x - 12
= x³ - x² + 7x² + 12x - 12
If we add all the coefficients, we get that the answer is 0. Thus, (x-1) is a factor of polynomial.
= x²(x-1) + 7x(x-1) + 12(x-1)
on re-arranging (x-1) as a common factor ;
= (x-1)(x²+7x+12) .........................................(1)
Now, we factorize (x² + 7x + 12)
(x² + 7x + 12)
= x² + 3x + 4x + 12
= x(x + 3) + 4(x + 3)
= (x + 4)( x +3) ..........................................(2)
On substituting for p(x) in 1 and 2, we get
(px) = (x-1)(x+4)(x+3)
= x³ - x² + 7x² + 12x - 12
If we add all the coefficients, we get that the answer is 0. Thus, (x-1) is a factor of polynomial.
= x²(x-1) + 7x(x-1) + 12(x-1)
on re-arranging (x-1) as a common factor ;
= (x-1)(x²+7x+12) .........................................(1)
Now, we factorize (x² + 7x + 12)
(x² + 7x + 12)
= x² + 3x + 4x + 12
= x(x + 3) + 4(x + 3)
= (x + 4)( x +3) ..........................................(2)
On substituting for p(x) in 1 and 2, we get
(px) = (x-1)(x+4)(x+3)
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.